RETRACTED : Aromaterapi Peppermint sebagai Terapi Non Farmakologi dalam Upaya Mengurangi Frekuensi Emesis Gravidarum pada Ibu Hamil Trimester I di Wilayah Kerja Puskesmas Pahandut Palangka Raya - Leni, Agusta; Meldawati, Meldawati; Kusvitasari, Hairiana (MASALIQ, 2023)
In 2021 the number of first trimester pregnant women who experienced emesis gravidarum in the Pahandut Palangka Raya Puskesmas Working Area was 793 people, while the first trimester pregnant women were 232 people (90%) of the 257 first trimester pregnant women. Aromatherapy that is safe and harmless to pregnant women. To determine the effect of peppermint aromatherapy on reducing the frequency of emesis gravidarum in I trimester pregnant women in the Pahandut Palangka Raya Health Center Working Area. Type of pre-experimental design research with one group pretest-postest design. The research population is 232 people. The sample technique uses purposive sampling. The sample was 15 respondents. Data analysis with Wilcoxon Signed Rank Test. The frequency of gravidarum emesis in I trimester pregnant women in the Pahandut Health Center Work Area before treatment was given a moderate category of 14 (93.3%) and the frequency of gravidarum emesis in I trimester pregnant women in the Pahandut Health Center Work Area before being given treatment was a mild category of 10 (66.6%). Wilcoxon Signed Rank Test results obtained a p-value of 0.001. There is an influence of peppermint aromatherapy as a non-pharmacological therapy in an effort to reduce the frequency of emesis gravidarum in pregnant women in the first trimester in the working area of the Pahandut Palangka Raya Health Center